Analisis Perubahan Penggunaan Lahan di Kota Denpasar dengan Metode NDVI (Normalize Difference Vegetation Index) - Fadilah Triani Putri; Ni Made Trigunasih; Putu Perdana Kusuma Wiguna (Fakultas Pertanian, Universitas Udayana, 2022)
Denpasar City is the capital city of Bali Province with a recorded population of 739,000 people in 2010. In 2020, the population will increase to 962,900 people, with a population increase of 1.01% per year.increase in population will have an impact on increasing the Impervious Surface Area (ISA) or watertight artificial structures, for example the area of built-up land. This land use change affects the green land cover in the Denpasar City area, so it is necessary to analyze land use changes in 2010 and 2020 using the Normalize Difference Vegetation Index. In 2010, the land cover for very dense class was 1795.43 ha, with dense land cover 2672, 85 ha, moderately dense 3520.59 ha, not dense 3749.36 ha and no vegetation 784.79 ha. In 2020, the land cover for very dense class is 1708.26 ha, with dense land cover 2287.99 ha, moderately dese class is 3326.15 ha, not dense 4519.29 ha and no vegetation 682.08 ha. The results of the NDVI analysis showed the highest land cover increase, namely the not dense class is 769.93 ha with the dominant land cover being residential or built-up land. This land use change occurs due to the increasing population of Denpasar City.